(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
ABSTRACT Artificial Intelligence (AI) introduces a new frontier of legal, ethical, and social challenges, especially regarding its ability to produce collective and diffuse impacts that transcend the limits of individual liability. The general objective of this article is to analyze the (in)capacity of Brazilian law to respond to collective damages caused by AI, under the ESG governance and digital citizenship framework. It seeks to understand how the national legal system, still structured around analog paradigms, can develop effective mechanisms for collective protection and technological accountability. The specific objectives are: (i) to identify normative and institutional gaps in AI regulation; (ii) to examine the role of collective protection as a tool for democratic and technological governance; and (iii) to propose guidelines for a procedural regime oriented towards technological and sustainable justice. The research is justified by the need for Law to keep pace with technological transformations without abandoning the protection of fundamental rights, especially in the face of the growing automation of decision-making processes and algorithmic opacity. The methodology used is deductive and interdisciplinary, combining bibliographic, documentary, and empirical analysis, based on reports from the National Council of Justice (CNJ, 2024), the Organization for Economic Cooperation and Development (OECD, 2024), the United Nations Educational, Scientific and Cultural Organization (UNESCO, 2024), the Massachusetts Institute of Technology (MIT, 2023), and the European Parliament (AI Act, 2024). The expected results point to the construction of a normative and institutional model of algorithmic governance anchored in ESG principles, public ethics, and shared responsibility. Keywords: Artificial Intelligence. Collective Protection. ESG. Civil Liability. Algorithmic Governance.